STRATEGY OF CLINICAL PRACTICE LEARNING OF MIDWIFER OF STUDENTS: A SCOPING REVIEW - Rahimah, Hayatul; Mufdlilah, Mufdlilah; Hakimi, Hakimi (Jurnal Kesehatan - STIKes Prima Nusantara, 2021)
Background:Clinical practice learning is the most important part of health education programs. The limitation of the presence of students at hospitals to avoid exposure to covid-19 causes the lack of training received by studentsObjective:The purpose of this study was to systematically map the results of research on clinical practice learning methods carried out by health professional education as learning recommendations during the Covid-19 pandemic.Method:This research was conducted with a five-stage review process, starting with searching for articles through relevant databases, namely Pubmed, Science Direct and Wiley, and finding 11 articles relevant to the inclusion criteria that have been determined.Result:Based on the review results, several clinical learning methods were found using E-learning through video, telehealth collaboration, and simulation based learning. There are several advantages and disadvantages to using each of these methods. Not all of these methods can be used as an evaluation of the student learning process. E-learning through videos can be done as a learning innovation to provide opportunities for students for patients with specific learning objectives.Conclusion:In conclusion, in practice there are clinical experiences that cannot be included by any method. Therefore, the standardization of student competencies is fulfilled by the Midwife Competency Test. However, clinical learning strategies in midwifery education can be done through E-learning with video conference, telehealth collaboration, and combination simulation methods with case studies which have the effectiveness to achieve certain learning objectives according to each method. In practice, information technology can be used as an innovation in distance learning. The implementation of this learning strategy requires good support and cooperation between institutions for clinical practice locations and the education institutions. And, Infrastructures need to be prepared to support the clinical practice learning process.